A microwave curing CDW based polymer stabilized soil and method of making same
Patent Information
- Application Number
- CN202610662191.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-14
- Publication Date
- 2026-09-04
AI Technical Summary
[0003]目前建筑废弃物主要是采用露天堆填或填埋的处理模式,这类粗放处置方式侵占大量土地资源并涉及征地补偿、运输处置等多项成本,还可能会引发填埋区域土质恶化及地表沉降与塌陷风险,需要经过长期自然沉降才能逐步恢复地质稳定
[0029] (1) The present invention scientifically proportions each raw material, organically combines the effective components, gives full play to the characteristics and synergistic effects of each component, and rationally adjusts the process parameters; the present invention has good immediate effect, good stability, and high compressive strength, and significantly improves the strength of waste geological materials in terms of physical and chemical effects.
Smart Images

Figure CN122685356A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of geotechnical engineering materials and solid waste treatment technology, and in particular to a microwave-cured CDW-based polymer-stabilized soil and its preparation method. Background Technology
[0002] Many old buildings are demolished to make way for new projects, generating a large amount of construction demolition waste (CDW). In addition, natural disasters such as war and earthquakes can also damage urban buildings, resulting in a large amount of construction waste such as tiles, red clay brick fragments, waste glass, and concrete blocks.
[0003] Currently, construction waste is mainly disposed of through open-air dumping or landfilling. This extensive disposal method consumes significant land resources and involves costs related to land acquisition compensation, transportation, and disposal. It may also lead to soil degradation and surface subsidence / collapse in the landfill area, requiring long-term natural settlement to gradually restore geological stability. Construction waste, such as glass and red bricks, is rich in elements like silicon and aluminum. Using it as raw material for geopolymers can improve soil mechanical properties. Furthermore, recycling construction waste effectively reduces dependence on natural resources, lowers environmental pollution, and reduces costs, making it an important pathway to sustainable development in the context of resource scarcity.
[0004] Microwave curing is an effective way to achieve rapid heating in a short period of time, and it has advantages such as improved reaction kinetics, low heat loss, uniform heating, and high energy efficiency. Numerous studies have shown that compared with traditional oven curing, microwave curing reduces the curing time from 28 days to just over ten minutes, greatly improves the strength of geopolymers, and may have an optimal curing range.
[0005] Therefore, by using microwave curing and adjusting the proportion of geopolymer-stabilized soil, these construction wastes, which are considered waste, can be rationally utilized as resources. Furthermore, when natural disasters such as earthquakes occur, available waste materials from the surrounding area can be used for rapid repair of roadbeds, which is in line with current policies and the advocacy of a low-carbon era. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing microwave-cured CDW-based polymer-solidified soil.
[0007] A type of polymer-solidified soil based on microwave curing CDW base comprises the following raw materials by mass percentage: 20-25% solidification material and 75-80% waste excavated geological materials; the solidification material includes: alkali activator and construction demolition waste, with a mass ratio of alkali activator to construction demolition waste of 1.4; the alkali activator is an aqueous solution containing sodium hydroxide and sodium silicate; the construction demolition waste includes: slag, glass powder, and red brick powder.
[0008] Preferably, the modulus of the alkali activator is 1.2-1.5.
[0009] More preferably, the concentration of NaOH in the alkali activator is 12 mol / L.
[0010] Preferably, the alkali activator is obtained by dissolving flake-shaped NaOH solid and white powdered anhydrous sodium silicate in distilled water.
[0011] More preferably, distilled water is heated to boiling and cooled to 60±5℃ to dissolve anhydrous sodium silicate powder to prepare a water glass solution. Then, flake-shaped sodium hydroxide solid is added to the solution. By adjusting the amount of sodium hydroxide added, the sodium ion concentration in the system is changed, thereby controlling the relative content of Na2O in the composite alkali-activated solution, and finally achieving precise adjustment of the water glass modulus.
[0012] Specifically, the flaky NaOH solid is of superior analytical grade, with a NaOH mass fraction of 98%, indicating high purity.
[0013] Specifically, the modulus of anhydrous sodium silicate powder is 3.4.
[0014] Preferably, the amount of building demolition waste mixed in is 10-30%.
[0015] Preferably, the building demolition waste comprises, by weight: 20-30% slag, 20-30% glass powder, and the remainder is red brick powder.
[0016] More preferably, the glass powder is obtained by crushing and grinding flat glass used in construction.
[0017] More preferably, the red brick powder is made from clay red bricks removed from abandoned buildings. The bricks are first crushed into small pieces with a hammer, then crushed by a pulverizer, and finally passed through a 200-mesh sieve.
[0018] Preferably, the slag is grade S105, light gray in color, fine in texture, with relatively uniform particles, and its main components are CaO, SiO2, Al2O3, etc.
[0019] Preferably, the building demolition waste also includes: microencapsulated calcium oxide, wherein the mass ratio of microencapsulated calcium oxide to slag is 5-10:20-30.
[0020] More preferably, microencapsulated calcium oxide is prepared by the following steps: adding silane coupling agent and carboxyl-terminated polyamide amine to calcium oxide powder and mixing evenly, stirring at 100-115℃ for 10-30 min under nitrogen protection, vacuum drying, adding the product and sodium oxidized alginate to anhydrous ethanol and stirring for 1-3 h, centrifuging, washing, and vacuum drying.
[0021] Microencapsulated calcium oxide utilizes calcium oxide encapsulated with silane coupling agents, carboxyl-terminated polyamide amines, and sodium alginate to form a slow-release core-shell structure, which can effectively delay hydration expansion and slowly release calcium ions. It works synergistically with calcium oxide in slag and promotes the formation of geopolymer gels with alkali activators. Under microwave curing, the microstructure is optimized, significantly improving the strength, stability, and durability of the solidified soil.
[0022] Specifically, the mass ratio of silane coupling agent, carboxyl-terminated polyamide amine, calcium oxide powder, and sodium alginate oxide is 1-2:1-2:20-40:1-3.
[0023] Specifically, the silane coupling agent is KH-570 coupling agent.
[0024] The above-mentioned method for preparing polymer-stabilized soil based on microwave-cured CDW base includes the following steps:
[0025] S1. Add water to the waste excavated geological materials according to the moisture content and stir into mud. Then add the building demolition waste and mix evenly. Next, add the alkali activator and mix evenly to form a uniform, non-layered geopolymer solidified soil slurry.
[0026] S2. Pour the geopolymer solidified soil slurry into the mold and vibrate for 30-60 seconds. Let it stand at room temperature for 22-26 hours. After demolding, microwave it for a certain period of time, and then perform standard curing.
[0027] Preferably, the microwave curing power is 100-500W, and the microwave curing time is 20-50 minutes.
[0028] Compared with existing technologies, the present invention has the following advantages:
[0029] (1) The present invention scientifically proportions each raw material, organically combines the effective components, gives full play to the characteristics and synergistic effects of each component, and rationally adjusts the process parameters; the present invention has good immediate effect, good stability, and high compressive strength, and significantly improves the strength of waste geological materials in terms of physical and chemical effects.
[0030] (2) In this process, the silica-alumina phase in the precursor depolymerizes and recombines under alkaline conditions to form a high-strength and dense structure. CaO in the slag participates in the reaction and is activated by the alkali-activated component and the silicate-activated component. It undergoes a hydration reaction with the alkali-activated component and the silicate-activated component to generate hydraulic minerals such as calcium silicate hydration gel (CSH) or calcium aluminum silicate gel (CASH), which helps to generate strength. Microwave high temperature will accelerate the reaction and generate secondary zeolite to fill cracks and enhance stability. It will also lead to the removal of structural water and the sintering and densification of the soil, thereby improving the strength. Therefore, the strength of this invention reaches more than 50% of the final effect at 0 days. Compared with cement-based solidified soil, the immediate strength after microwave curing can reach 41.84-57.58% of the 28-day curing strength of traditional cement materials.
[0031] (3) The preparation method of the present invention is simple and convenient. By reasonably adjusting the process parameters and selecting the optimal range of process parameters, the raw materials are more firmly bonded together, so that the solidified soil achieves the best effect. By adjusting the selection and ratio of material components, it can be adapted to various engineering application scenarios, including but not limited to: roadbed base course, various backfill materials, soil improvement, surface cover, etc. At the same time, suitable composite admixture components are added to meet the needs of various practical projects.
[0032] (4) This invention can simultaneously digest construction waste to a great extent using slag, glass powder and red brick powder, and can effectively solve the land and environmental problems caused by the dumping of large quantities of solid waste and construction waste.
[0033] (5) This invention utilizes a complete solid waste system to treat construction waste, achieving the comprehensive utilization goal of "treating waste with waste", which is in line with the economic concept of low-carbon, green and environmentally friendly development, and realizes the green, efficient, high-quality, high-value, large-scale and comprehensive utilization of my country's "large-scale solid waste".
[0034] (6) This invention can effectively replace cement, a high-energy-consuming and high-carbon-emission material, for the treatment of construction waste, and can avoid the greenhouse gas emissions generated by cement. This is in line with the concept of environmental protection and responds to the call of the national dual-carbon target. Attached Figure Description
[0035] Figure 1 Comparison of unconfined compressive strength of solidified soil with 15% CDW content under different microwave curing conditions.
[0036] Figure 2 Comparison of unconfined compressive strength of solidified soil with 20% CDW content under different microwave curing conditions.
[0037] Figure 3 The graph shows the change in the strength of the solidified soil obtained in Examples 11, 26, 1, and 2 as a function of age.
[0038] Figure 4 The graph shows the change in the strength of the solidified soil obtained in Examples 26 and 31-33 as a function of age. Detailed Implementation
[0039] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0040] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0041] The physical properties of the waste excavated geological materials used are as follows: Liquid limit (w L )44.5%, plastic limit (w P 25.7%, plasticity index (I P 18.8%; Particle content of different sizes: sand (>0.074mm) 1.4%, powder (0.005~0.074mm) 77.4%, clay (<0.005mm) 21.2%. The carboxyl-terminated polyamide amine (PAMAM-COOH, G3.0) used below was purchased from Hangzhou Xinqiao Biotechnology Co., Ltd.
[0042] Examples 1-30
[0043] The proportions of the solidification material and the waste excavated geological materials used are shown in Table 1. The solidification material consists of an alkali activator and construction demolition waste in a mass ratio of 1.4:1; the alkali activator is an aqueous solution containing sodium hydroxide and sodium silicate with a modulus of 1.2; the construction demolition waste consists of slag, glass powder, and red brick powder in a mass ratio of 25:25:50.
[0044] The steps for preparing the alkali activator in each embodiment are as follows: Distilled water is heated to boiling and cooled to 60±5℃ to dissolve anhydrous sodium silicate powder to prepare a water glass solution. Then, flake sodium hydroxide solid is added to the solution. By adjusting the amount of sodium hydroxide added, the sodium ion concentration in the system is changed, thereby controlling the relative content of Na2O in the alkali activator and finally achieving precise adjustment of the water glass modulus.
[0045] The preparation steps of each embodiment are as follows: First, pre-treat the waste excavated geological materials: Pass the dried and crushed excavated soil through a 2mm standard sieve. Weigh a certain amount of soil according to the preset initial moisture content, add the corresponding amount of water, and stir into a slurry. First, use a trowel to initially mix evenly, then use a small mixer to stir at high speed for 2 minutes to ensure uniform moisture distribution. Next, put slag, glass powder, and red brick powder into a mixing container and mix thoroughly, repeatedly mixing for 5 minutes until the powder color is uniform and there is no obvious particle agglomeration. Pour the above-mentioned evenly mixed construction demolition waste and soil slurry into the same container, stir until initially combined, add an alkali activator, and continue stirring with a small mixer for 5 minutes to finally form a homogeneous mixture. 1. Geopolymer-stabilized soil slurry without stratification: Pour the geopolymer-stabilized soil slurry into the mold. After each layer is poured (the thickness is about 1 / 3 of the mold height), immediately place the mold on a vibration table and vibrate for 30-60 seconds (vibration frequency 50Hz) to ensure the slurry is dense and remove internal air bubbles. After all the slurry has been poured, use a scraper to smooth the top surface of the mold and let it stand at room temperature for 24 hours. After the sample has initially solidified, demold it. Place the demolded sample in a microwave oven (without sealing) for microwave curing. After curing, remove the sample and let it cool naturally to room temperature before use. Place it in a standard curing chamber and cure it to the specified age under the conditions of 95% relative humidity and (20±2)℃.
[0046] The differences between the various embodiments are shown in Table 1.
[0047] Table 1 Dosage Implementation Schemes for Each Example
[0048] 1 <![CDATA[1.0w L ]]> 15% 100W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 2 <![CDATA[1.0w L ]]> 15% 100W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 3 <![CDATA[1.0w L ]]> 15% 100W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 4 <![CDATA[1.0w L ]]> 15% 200W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 5 <![CDATA[1.0w L ]]> 15% 200W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 6 <![CDATA[1.0w L ]]> 15% 200W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 7 <![CDATA[1.0w L ]]> 15% 300W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 8 <![CDATA[1.0w L ]]> 15% 300W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 9 <![CDATA[1.0w L ]]> 15% 300W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 10 <![CDATA[1.0w L ]]> 15% 400W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 11 <![CDATA[1.0w L ]]> 15% 400W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 12 <![CDATA[1.0w L ]]> 15% 400W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 13 <![CDATA[1.0w L ]]> 15% 500W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 14 <![CDATA[1.0w L ]]> 15% 500W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 15 <![CDATA[1.0w L ]]> 15% 500W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 16 <![CDATA[1.0w L ]]> 20% 100W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 17 <![CDATA[1.0w L ]]> 20% 100W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 18 <![CDATA[1.0w L ]]> 20% 100W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 19 <![CDATA[1.0w L ]]> 20% 200W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 20 <![CDATA[1.0w L ]]> 20% 200W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 21 <![CDATA[1.0w L ]]> 20% 200W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 22 <![CDATA[1.0w L ]]> 20% 300W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 23 <![CDATA[1.0w L ]]> 20% 300W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 24 <![CDATA[1.0w L ]]> 20% 300W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 25 <![CDATA[1.0w L ]]> 20% 400W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 26 <![CDATA[1.0w L ]]> 20% 400W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 27 <![CDATA[1.0w L ]]> 20% 400W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 28 <![CDATA[1.0w L ]]> 20% 500W×20min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 29 <![CDATA[1.0w L ]]> 20% 500W×35min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 30 <![CDATA[1.0w L ]]> 20% 500W×50min 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test
[0049] Comparative Examples 1-2
[0050] The cement (ordinary Portland cement, grade 42.5, purchased from a cement plant in Nanjing, Jiangsu Province) and the waste excavated geological materials were used according to the mass ratio shown in Table 2. The differences between the groups are shown in Table 2.
[0051] Table 2 Implementation Scheme for Dosage of Each Comparative Proportion
[0052] 1 <![CDATA[1.0w L ]]> 15% 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test 2 <![CDATA[1.0w L ]]> 20% 0 / 1 / 3 / 7 / 14 / 28d Unconfined compressive strength test
[0053] The comparative example differs from the embodiment, employing standard curing as follows: The dried and crushed excavated soil was passed through a 2mm standard sieve. A measured amount of soil was weighed according to the preset initial moisture content, and the corresponding amount of water was added and stirred into a slurry. The slurry was first initially mixed evenly with a geotextile knife, then stirred at high speed for 2 minutes using a small mixer to ensure uniform moisture distribution. Cement and soil slurry were poured into the same container and stirred until initially combined. Then, the mixture was stirred for 5 minutes using a small mixer to finally form a uniform, non-layered solidified soil slurry. The solidified soil slurry was poured into the mold in layers. After each layer (approximately 1 / 3 the height of the mold), the mold was immediately placed on a vibrating table and vibrated for 30-60 seconds (vibration frequency 50Hz) to ensure the slurry was dense and to remove internal air bubbles. After all the slurry was poured, the top surface of the mold was leveled with a scraper and left to stand at room temperature for 24 hours. After the sample had initially solidified, it was demolded. The demolded sample was placed in a standard curing chamber and cured at a relative humidity of 95% and a temperature of (20±2)℃ until the specified age.
[0054] In practical engineering, unconfined compressive strength is one of the most important mechanical performance indicators, serving as a key metric for determining whether a material can effectively serve in real-world applications. Specifically, unconfined compressive strength refers to the maximum axial stress a material can withstand when its sides are unconstrained, allowing for rapid and accurate testing of its mechanical properties.
[0055] like Figure 1 , Figure 2 and Figure 3 As shown, under the same abandoned excavation geological materials, alkali activation conditions, and curing conditions, the instantaneous strength of the solidified soil obtained by using this invention, without subsequent curing, can reach 1-2 MPa after microwave curing, corresponding to more than 50% of its 28-day unconfined compressive strength. The immediate strength after microwave curing can reach 41.84-57.58% of the 28-day strength of traditional cement-cured soil, and more than 90% of the 28-day strength of traditional cement-cured soil in 14 days. The early strength and the strength development coefficient over age are much higher than those of traditional cement-cured soil, which can achieve the construction requirements of high strength with short-term curing. Moreover, the compressive strength first increases and then decreases with the increase of microwave power and microwave curing time. After the generation of macroscopic cracks, the compressive strength can still maintain a certain growth. The results of unconfined compressive strength are better than those of traditional cement-cured soil.
[0056] Analysis of the reasons: The strength index of the solidified soil obtained by this invention is superior to that of ordinary silicate cement materials because the main product of the geopolymer solidified soil, which uses slag, glass powder, and red brick powder as precursors, is an amorphous sodium-based aluminosilicate gel (NASH) with a three-dimensional network structure. This gel is formed by the depolymerization and recombination of the silica-alumina phase in the precursors under alkaline conditions, exhibiting high strength and density. Simultaneously, CaO from the slag participates in the reaction, generating calcium silicate hydration gel (CSH) or calcium aluminosilicate gel (CASH). These gels coexist with NASH, forming a mixed gel phase. Some of these amorphous gels adhere to the soil surface, encapsulating soil particles, while others exist between soil particles, filling soil pores, cementing soil particles, and forming a cohesive soil mass, thereby improving the structure of the solidified soil. With the increase of admixture dosage, the amount of various hydration products and gel products generated increases, and the strength of the solidified soil also increases. In the early stage, more C-(A)-SH and NASH gel substances are generated through geological polymerization and hydration reactions, which is beneficial to the early strength development. Microwave high temperature accelerates the reaction, which will produce secondary zeolite to fill cracks and enhance stability. It will also lead to the removal of structural water and the sintering and densification of the soil, thereby improving the strength.
[0057] Example 31
[0058] The difference from Example 26 is that the building demolition waste is composed of slag, glass powder, microencapsulated calcium oxide, and red brick powder in a mass ratio of 25:25:7.5:42.5.
[0059] Microencapsulated calcium oxide was prepared by the following steps: 1 part by weight of KH-570 coupling agent and 2 parts by weight of carboxyl-terminated polyamide amine were added to 20 parts by weight of calcium oxide powder and mixed evenly. The mixture was stirred at 115°C for 10 min under nitrogen protection at a stirring speed of 200 r / min and then vacuum dried. The product was then added to 200 parts by weight of anhydrous ethanol and stirred for 1 h at a stirring speed of 300 r / min. The mixture was then centrifuged, washed, and vacuum dried.
[0060] Example 32
[0061] The difference from Example 31 is that the microencapsulated calcium oxide is prepared by the following steps: 2 parts by weight of KH-570 coupling agent and 1 part by weight of carboxyl-terminated polyamide amine are added to 40 parts by weight of calcium oxide powder and mixed evenly. The mixture is stirred at 100°C for 30 min under nitrogen protection at a stirring speed of 100 r / min and then vacuum dried. The product is added to 100 parts by weight of anhydrous ethanol with 3 parts by weight of oxidized sodium alginate and stirred for 3 h at a stirring speed of 100 r / min. The mixture is then centrifuged, washed, and vacuum dried.
[0062] Example 33
[0063] The difference from Example 31 is that the microencapsulated calcium oxide was prepared by the following steps: 1.5 parts by weight of KH-570 coupling agent and 1.5 parts by weight of carboxyl-terminated polyamide amine were added to 30 parts by weight of calcium oxide powder and mixed evenly. The mixture was stirred at 110°C for 20 min under nitrogen protection at a stirring speed of 150 r / min and then vacuum dried. The product was then added to 150 parts by weight of anhydrous ethanol and stirred for 2 h at a stirring speed of 200 r / min. The mixture was then centrifuged, washed, and vacuum dried.
[0064] like Figure 4 As shown, in Examples 31-33, microencapsulated calcium oxide was used to prepare solidified soil, and the unconfined compressive strength at each age was better than that in Example 26; while in Example 33, the unconfined compressive strength at each age was better than that of the other groups.
[0065] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope, and without requiring unnecessary experiments. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including changes made using conventional techniques known in the art that depart from the scope disclosed herein.
Claims
1. A method for solidifying soil based on microwave-cured CDW (CDW) base polymer, characterized in that, Its raw materials, by weight percentage, include: 20-25% solidification materials and 75-80% waste excavated geological materials; The curing materials include: alkali activator and construction demolition waste, with a mass ratio of alkali activator to construction demolition waste of 1.4; The alkaline activator is an aqueous solution containing sodium hydroxide and sodium silicate; demolition waste includes: slag, glass powder, and red brick powder.
2. The microwave-cured CDW-based polymer-stabilized soil according to claim 1, characterized in that, Demolition waste by weight includes: 20-30% slag, 20-30% glass powder, and the remainder is red brick powder.
3. The microwave-cured CDW-based polymer-stabilized soil according to claim 1, characterized in that, The modulus of the alkali activator is 1.2-1.
5.
4. The microwave-cured CDW-based polymer-stabilized soil according to claim 1, characterized in that, The content of building demolition waste is 10-30%.
5. The microwave-cured CDW-based polymer-stabilized soil according to claim 1, characterized in that, The slag type grade is S105.
6. The microwave-cured CDW-based polymer-stabilized soil according to claim 1, characterized in that, Construction demolition waste also includes: microencapsulated calcium oxide, with a mass ratio of microencapsulated calcium oxide to slag of 5-10:20-30; Microencapsulated calcium oxide is prepared by the following steps: silane coupling agent and carboxyl-terminated polyamide amine are added to calcium oxide powder and mixed evenly. The mixture is stirred at 100-115℃ for 10-30 min under nitrogen protection and then vacuum dried. The product and sodium alginate oxide are added to anhydrous ethanol and stirred for 1-3 h. The mixture is then centrifuged, washed, and vacuum dried.
7. The microwave-cured CDW-based polymer-stabilized soil according to claim 6, characterized in that, The mass ratio of silane coupling agent, carboxyl-terminated polyamide amine, calcium oxide powder, and sodium alginate oxide is 1-2:1-2:20-40:1-3.
8. The microwave-cured CDW-based polymer-stabilized soil according to claim 6, characterized in that, The silane coupling agent is KH-570 coupling agent.
9. A method for preparing microwave-cured CDW-based polymer-stabilized soil as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Add water to the waste excavated geological materials according to the moisture content and stir into mud. Then add the building demolition waste and mix evenly. Next, add the alkali activator and mix evenly to form a geopolymer solidified soil slurry. S2. Pour the geopolymer solidified soil slurry into the mold and vibrate for 30-60 seconds. Let it stand at room temperature for 22-26 hours. After demolding, microwave curing is performed for a certain period of time, followed by standard curing.
10. The method for preparing microwave-cured CDW-based polymer-stabilized soil according to claim 9, characterized in that, Microwave curing power is 100-500W, and microwave curing time is 20-50 minutes.